Pengembangan Sistem Pertanian Siklus-Bio Terpadu untuk Peningkatan Produktivitas Ternak Sapi pada Kelompok Ternak Desa Margoagung, Sayegan, Sleman, Yogyakarta - Cahyono Agus Dwikoranto; Ali Agus; Bambang Suhartanto (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2015)
Integrated Bio-Cycle Farming System was developed by KP4 University Farm UGM Yogyakarta should be implemented to the communities. The community service for implementation of science and technology starting with an MOU between KP4 and the government of Margoagung village, especially Farmer Group RUKUN, Margoagung, Seyegan, Sleman that requiring transferred technology. Community service programs and assistance through the transfer of integrated bio-cycle farming system were done through development of burgers feed technology for cows, solid fertilizer, liquid fertilizer, and waste treatment technology for biogas. This activity also involves 22 students from various faculties at UGM for 2 months in the field. The technology is transferred directly by experts from GMU and directly accompanied intensively by student. Enthusiastic, productivity, quantity, quality and continuity of integrated farming were very important for a better life and environment.